Cloning and Expression of Leptospiral Immunoglobulin Like B Gene and Use of The Recombinant Antigen for The Diagnosis of Bovine and Caprine Leptospirosis - Deneke, Yosef; Deb, Rajib (International Journal of Applied Sciences and Biotechnology, 2020)
In the present study recombinant LigB protein is employed in latex agglutination test, which is a cross reacting lipoprotein able to detect acute infection caused by any pathogenic leptospiral serovars. It was employed for serodiagnosis of leptospirosis. The 46KDa 6X His tagged LigB protein, obtained by IPTG induction of recombinant E. coli M15 cells containing the N-terminal region of LigB gee in PQE30 expression vector, was purified by Ni-NTA affinity chromatography and adsorbed on latex bead surface for performing latex agglutination test against Leptospirosis suspected field sea. Western blot confirmed that rLigB is an immunodominant protein against which antibodies are produced during active infection. A total of 453 field sera, including 432 bovine sera, 18 caprine sera and three sera samples of buffalo bull collected post-mortem following death the animal from Indian Veterinary Research institute (IVRI) were tested using rLigB based LAT. The result showed that 300 sera were tested positive by rLigB based LAT, which were reconfirmed using microscopic agglutination test (MAT). The results from LAT were in concordance with MAT. In conclusion, under laboratory and field conditions, rLigB based LAT is a rapid, pen site, reliable diagnostic tool of high sensitivity and specificity for the detection of Leptospirosis. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 146-153